From childhood to adolescence: Development of binge eating and the prospective role of self-regulation - Nele Westermann; Annette M. Klein; Robert Busching; Petra Warschburger (Journal of Eating Disorders)
Abstract Background Research shows that binge eating often starts in childhood or adolescence, but its development remains largely unexplored. Additionally, while cross-sectional studies link self-regulation to binge eating, longitudinal research is lacking. Therefore, this study examined the development of binge eating and self-regulation as a potential predictor for this development in a community sample. Methods A total of N = 1660 children were assessed at four time points spanning ages 6–11, 7–11, 9–13, and 16–21. The assessment of self-regulation encompassed emotional reactivity, working memory updating, cognitive flexibility, inhibition, inhibitory control, planning behavior, affective decision-making, anger regulation, and as appetite self-regulation, satiety responsiveness, emotional overeating, food responsiveness, and external eating, using computerized tasks, teacher- and parent-reports. Binge eating was modeled by child-reported loss of control eating, overeating, and eating in the absence of hunger. A latent change score model was used to evaluate intra- and interindividual differences in binge eating across middle childhood and adolescence. Self-regulation facets were regressed on changes in binge eating. Results Results indicated a decrease in binge eating at the beginning of middle childhood, followed by a stagnation and then an increase during adolescence, with significant interindividual differences in these changes. Higher planning behavior, inhibitory control, and cognitive flexibility predicted decreases in binge eating during middle childhood, while higher satiety responsiveness unexpectedly predicted an increase in binge eating during adolescence. Results remained the same after controlling for body weight. Conclusions Our findings highlight adolescence as a critical period for binge eating prevention, with planning behavior, inhibitory control, and cognitive flexibility acting as protective factors in middle childhood. The longitudinal data underscore the importance of self-regulation in the development of binge eating.